Síntese de uma Zn(II)-porfirina hidrossolúvel do tipo A3B como fotossensibilizador para inativação fotodinâmica de Candida albicans - Oliveira, Maria Eduarda de Lima (2024)
Water-soluble Zn(II) porphyrins derived from 2-N-alkylpyridylporphyrins (ZnTalkyl-2PyP4+) have been extensively investigated as photosensitizers in the photodynamic inactivation of microorganisms. Zn(II) porphyrins show in vivo efficacy due to a combination of photophysical and biodistribution properties. Our group recently introduced a new class of [ZnA3B]3+-type, cationic meso-substituted Zn(II) porphyrins, with A representing the 2-N-methylpyridyl group and B representing the O-alkylvanillin group. In this study, 5-(3,4-dimethoxyphenyl)-10,15,20-tris(N-methylpyridinium-2yl)porphyrinatezinc(II) chloride (ZnMVanTriM-2-PyPCl3) was synthesized through simultaneous alkylation of the pyridyl and vanillin moieties of 5-(3-methoxy-4hydroxyphenyl)-10,15,20-tris(2-pyridyl)porphyrin (H2VanTri-2-PyP), resulting in the formation of 5-(3,4-dimethoxyphenyl)-10,15,20-tris(N-methylpyridinium-2yl)porphyrin chloride (H2MVanTriM-2-PyPCl3), followed by subsequent metallation with Zn(II). ZnMVanTriM-2-PyP3+ was characterized by CCD-SiO2, UV-vis absorption spectroscopy, fluorescence spectroscopy, 1H NMR spectroscopy, and finally by highresolution mass spectrometry (ESI-HRMS). As expected, determination of the n-octanolwater partition coefficient (log Pow) for ZnMVanTriM-2-PyP3+ indicated that this [ZnA3B]3+-type ZnP is more lipophilic than its structural [ZnA4]4+-type prototype, mesotetrakis(N-methylpyridinium-2-yl)porphyrinatezinc(II) (ZnTM-2-PyP4+). ZnMVanTriM2-PyP3+ and ZnTM-2-PyP4+ were evaluated as photosensitizers in the photodynamic inactivation of Candida albicans. The greater activity of ZnMVanTriM-2-PyP3+ was attributed to its higher lipophilicity. This study demonstrated for the first time, as proof of concept in a pathogenic biological model, that [ZnA3B]3+-type Zn(II) porphyrins designed by our group are good candidates for the development of a new class of photosensitizers and suggested that the analogous Mn(III) porphyrins, of interest as redox-active therapeutic agents, may also be biologically accessible.